2018
DOI: 10.1097/iae.0000000000001677
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Autonomic Regulation of the Choroid in Central Serous Chorioretinopathy

Abstract: We demonstrated that choroidal thickness increased in response to increased perfusion pressures in patients with CSC and not in normal controls. These findings likely represent an autonomic dysregulation of choroidal blood flow in patients with CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The researchers found that, rather than Sattler's layer, Haller's layer leads to increased CT in patients with ICSCR, a finding that supports the view that focal occlusion at the level of the choriocapillaris, which is considered to be the primary cause of ICSCR, may not lead to increased CT (27). A recent study reported that the choriocapillaris and CT values of patients with ICSCR are significantly thicker than those of healthy controls in response to increased perfusion pressure in patients with ICSCR connected to transitioning from an upright to a supine position (28). The researchers suggested that the autoregulatory response is presumably better in the choriocapillaris layer than in the Haller's and Sattler's layers that consist of larger blood vessels (28).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The researchers found that, rather than Sattler's layer, Haller's layer leads to increased CT in patients with ICSCR, a finding that supports the view that focal occlusion at the level of the choriocapillaris, which is considered to be the primary cause of ICSCR, may not lead to increased CT (27). A recent study reported that the choriocapillaris and CT values of patients with ICSCR are significantly thicker than those of healthy controls in response to increased perfusion pressure in patients with ICSCR connected to transitioning from an upright to a supine position (28). The researchers suggested that the autoregulatory response is presumably better in the choriocapillaris layer than in the Haller's and Sattler's layers that consist of larger blood vessels (28).…”
Section: Discussionsupporting
confidence: 55%
“…A recent study reported that the choriocapillaris and CT values of patients with ICSCR are significantly thicker than those of healthy controls in response to increased perfusion pressure in patients with ICSCR connected to transitioning from an upright to a supine position (28). The researchers suggested that the autoregulatory response is presumably better in the choriocapillaris layer than in the Haller's and Sattler's layers that consist of larger blood vessels (28).…”
Section: Discussionmentioning
confidence: 99%
“…In CSC this regulation may be failing, suggesting dysregulation of choroidal vascular mechanisms of control. 29 By contrast, retinal vessels lack of extrinsic autonomic control. Similarly to the brain where neuronal processes are associated with intraparenchymal vessels and regulate blood flow, autonomic receptors are intrinsic on retinal vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In others, the etiology appears to be choroidal dysfunction, particularly involving choroidal circulation which is under autonomic control. [ 3 4 5 6 7 8 ] Autonomic dysfunction such as heart rate variability and sympathetic-parasympathetic imbalance have been reported in CSC. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 5 6 7 8 ] Autonomic dysfunction such as heart rate variability and sympathetic-parasympathetic imbalance have been reported in CSC. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%